Lipid accumulation product is an effective predictor of metabolic syndrome in non-obese women with polycystic ovary syndrome - Han, Wenju; Zhang, Meiwei; Wang, Haiyan; Yang, Yitian; Wang, Lei (Frontiers in Endocrinology, 2024)
Objective: To explore the correlation of lipid accumulation product (LAP) with metabolic syndrome (MS), and to assess the predictive value of LAP for MS risk in polycystic ovary syndrome (PCOS) with different body mass index (BMI).Methods: A total of 242 PCOS women and 150 controls were recruited and divided into normalweight, overweight and obese groups, then further divided into MS and without MS subgroups.Clinical and anthropometric variables and laboratory results were recorded. LAP was calculated from waist circumference (WC) and triglyceride using sex-specific formulae. Logistic regression analysis and receiver operating characteristic (ROC) curve were applied to determine and analyze the predictive value of LAP for MS.The prevalence of MS among PCOS women was 45.04%, which was significantly higher than that of the controls (10%). Stratified by BMI, the incidence of MS in the normal-weight, overweight, and obese PCOS groups were 15.58%, 41.43% and 71.58%, respectively. Logistic regression analysis displayed that LAP was an independent risk factor for MS in both normalweight and overweight groups, however, results were not significant in the obese group. ROC curve analysis showed that LAP had outstanding discriminating index for MS in normal-weight (AUC=0.960, cut-off value=42.5) and overweight (AUC=0.937, cut-off value=47.93) PCOS patients, with a sensitivity of 0.917/0.931 (normal-weight/overweight) and a specificity of 0.969/0.854 (normal-weight/overweight), respectively.Normal-weight and overweight PCOS patients also have a fairly incidence of MS, and should receive as much attention as obese companion. Compared to applying multiple clinical indicators, LAP is more convenient and enables acquiring early and accurate diagnoses to MS among non-obese PCOS patients using fewer MS markers.